Моделювання роботи багатоканальних СМО з урахуванням відмов - Дехтярук, М.Т. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2009)
The article is devoted to modern computer information technologies. The system of imitation design GPSS World is considered, with the purpose of design of work of the multichannel queuing systems taking into account the refusals. Computation of middle employment of channels of service and middle employment of point of
renewal is conducted and also maximal length of turn on renewal of channels of service.